EXPLORING HOW LEADERSHIP SHAPES THE LINK BETWEEN MEMBER PARTICIPATION AND CO-OPERATIVE PERFORMANCE: A CONCEPTUAL - Mohd Noor, Azianis; Ismail, Mohammad; Azmi, Siti Nurulaini; Zawawi, Nur Fadiah Mohd; Mohamad, Nurul Muna; Sidik, Mohamad Hazeem (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2026)
This conceptual paper examines the relationship between member participation and co-operative performance, emphasizing leadership as a moderating factor. While member participation is often recognized as the lifeblood of co-operatives, its impact on performance is not uniform and may be contingent upon leadership quality. Drawing on Agency Theory, Stakeholder Theory, the Resource-Based View, and leadership theories, the paper proposes a framework in which member participation contributes positively to financial and non-financial performance, but the strength of this relationship depends on the presence of effective leadership. Leadership traits such as inclusivity, vision, empathy, and coaching are argued to enhance accountability, foster shared purpose, and build member capacity, thereby amplifying the benefits of participation. The study develops three hypotheses: (1) member participation positively influences co-operative performance; (2) leadership positively influences cooperative performance; and (3) leadership moderates the participation–performance relationship. This paper contributes theoretically by extending cooperative governance models and practically by providing insights for managers and policymakers on the strategic role of leadership development. It is among the first studies to position leadership as a moderating factor in the relationship between member participation and cooperative performance within ASEAN cooperatives. Future empirical studies are recommended to validate the proposed framework across diverse co-operative contexts.